Aberrant Expression of Sprouty2 In Human Colon Cancer - BAESMAT, Ayriana Safari; BAYRAKDAR, Berna (Clinical Medicine And Health Research Journal, 2024)
Purpose: The study investigates the role of Sprouty2 (SPRY2) in colorectal cancer (CRC) cell function. It found that SPRY2 inhibits the RAS/MAPK/ERK pathway and promotes cancer invasion in KRAS-WT CRC. However, it did not significantly alter p-ERK levels, cell proliferation, or invasion in KRAS-mutant CRCs. High SPRY2 expression was associated with shorter cancer-specific survival in both KRAS-WT and KRAS-mutant CRC patients. The study suggests that SPRY2 may promote invasion and progression in both types of CRC. Methods: The gene expression data were retrieved from Gene Expression Omnibus (GEO). Fold change, p.value t-test and David Functional analysis, hierarchical clustering was performed. Results: In this study, we identified altered genes involved in SPRY2 mutation in the colon and the relevant pathways to understand whether the SPRY2 mutation changes cancer progression. 4 genes of 5 genes were downregulated following the mutation in colon cancer cells. We identified a network between these genes and pathways they belong to. Pathway analysis showed that these genes are mostly associated with cancer cell proliferation. Conclusion: MAL2, ESRP1, CDH3, CXCL14 and CDH1 genes were found to be associated with in SPRY2 mutation in colon cancer pathogenesis. Almost all these genes are effective in the proliferation of cancer cells, especially during the SPRY2 mutation process. Therefore, it is hypothesized that downregulation or upregulation of these genes may affect colon cancer pathogenesis by reducing cell proliferation. And it is predicted that SPRY2 mutation may be an important factor for colon cancer.